Neural correlates of phonological processing: Disrupted in children with dyslexia and enhanced in musically trained children. (November 2018) - Zuk, Jennifer; Perdue, Meaghan V.; Becker, Bryce; Yu, Xi; Chang, Michelle; Raschle, Nora Maria; Gaab, Nadine
Highlights: First fMRI investigation of phonological processing in musically trained children. Greater bilateral activation with music training in regions disrupted in dyslexia. Implications for music training to support compensatory neural network in dyslexia. Abstract: Phonological processing has been postulated as a core area of deficit among children with dyslexia. Reduced brain activation during phonological processing in children with dyslexia has been observed in left-hemispheric temporoparietal regions. Musical training has shown positive associations with phonological processing abilities, but the neural mechanisms underlying this relationship remain unspecified. The present research aims to distinguish neural correlates of phonological processing in school-age typically developing musically trained children, musically untrained children, and musically untrained children with dyslexia utilizing fMRI. A whole-brain ANCOVA, accounting for gender and nonverbal cognitive abilities, identified a main effect of group in bilateral temporoparietal regions. Subsequent region-of-interest analyses replicated temporoparietal hypoactivation in children with dyslexia relative to typically developing children. By contrast, musically trained children showed greater bilateral activation in temporoparietal regions when compared to each musically untrained group. Therefore, musical training shows associations with enhanced bilateral activation of left-hemispheric regions known to be important for reading. Findings suggest that engagement of these regions through musical training may underlie the putative positive effects of music on reading development. This supports the hypothesis that musical training may facilitate the development of a bilateral compensatory neural network, which aids children with atypical function in left-hemispheric temporoparietal regions.